1977
DOI: 10.2170/jjphysiol.27.525
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physical Characteristics, Body Temperature and Basal Metabolism Between Thai and Japanese in a Neutral Temperature Zone

Abstract: The aim of this research is to compare the physical status, basal metabolism and some other physiological characteristics between native Thai in Bangkok, Thailand, and native Japanese in Japan, and discuss the results regarding acclimatization to tropical climate. Measurements of the Thai were made in September in Bangkok, while those of native Japanese were done in August at Nishinomiya(Japan). The subjects were adult males(20-22 years old)in both cases. Physically the Thai are generally a little shorter and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Comparisons between Thais and Japanese (Matsumoto et al 1993), Malaysians and Japanese (Saat et al 2005) and Malaysians and Koreans (Lee et al 2004(Lee et al , 2009) have been performed without matching morphological characteristics between groups. Morphological variation itself resulted in different basal metabolism (Hori et al 1977;Taylor 2006;Tipton et al 2008). Individual morphological characteristics (Hori and Ihzuka 1986) such as body surface area (BSA) to body mass ratio (Havenith and Middendorp 1990) exert significant influences on individual responses to heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons between Thais and Japanese (Matsumoto et al 1993), Malaysians and Japanese (Saat et al 2005) and Malaysians and Koreans (Lee et al 2004(Lee et al , 2009) have been performed without matching morphological characteristics between groups. Morphological variation itself resulted in different basal metabolism (Hori et al 1977;Taylor 2006;Tipton et al 2008). Individual morphological characteristics (Hori and Ihzuka 1986) such as body surface area (BSA) to body mass ratio (Havenith and Middendorp 1990) exert significant influences on individual responses to heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…For example, certain patient populations have been identified to be more sensitive to heat-related injury (e.g., elderly, females, and patients with decreased mobility or dementia, patients on medications that affect thermoregulation (e.g., diuretics or anticholinergics), and patients with disorders that compromise thermoregulation (e.g., obesity, hypertension, pulmonary disease, diabetes)) [33,34]. Also, individual-level differences may also explain these differences, such as individual climate adaptability to one's surrounding environment [35]. A Japanese study found that men who lived in hot subtropical zone and moved to colder temperate zones showed superior signs of heat adaptation than those who lived in the temperate region alone (e.g., less skinfold thickness (e.g., upper arm-5.3 ± 2.3 vs. 7.7 ± 3.2mm, p < 0.001) and more effective sweating with less salt wasting (0.022 ± 0.004 vs. 0.029 ± 0.008 mEq/l, p < 0.05)) [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, human adaptation to temperature change can be affected by factors such as age, sex, ethnicity, thermal environment during childhood, and body fat ratio (Davies, 1979;Hori et al, 1977;Kenney and Munce, 2003;Sato and Dobson, 1970;Taylor and Machado-Moreira, 2013;Wijayanto et al, 2012;Yousef et al, 1984). Furthermore, human heat tolerance can vary depending on humidity, amplitude of temperature, and history of heat exposure (Havenith et al, 1998).…”
Section: Discussionmentioning
confidence: 99%